Revenue Recognition Case Study Based on Financial Accounting Standards Statements at PT. Prambanan Dwipaka: Studi Kasus Pengakuan Pendapatan Berdasarkan Pernyataan Standar Akuntansi Keuangan Pada PT. Prambanan Dwipaka - Sofia Azizatun Niza; Khojanah Hasan; Zaenuddin Zaenuddin (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The construction sector is characterized by complex, long-term contracts and uncertainty, making revenue recognition a critical aspect for the reliability of financial statements. Since the enactment of Statement of Financial Accounting Standards (PSAK) 72 in 2020 as an adoption of International Financial Reporting Standards (IFRS) 15, construction companies in Indonesia are required to align their accounting practices with the principles of control and performance obligations. This case study examines the implementation of PSAK 72 at PT. Prambanan Dwipaka using a qualitative approach through interviews, observations, and document analysis. The study results indicate that the company has attempted to systematically implement the five stages of PSAK 72, although it still faces obstacles in identifying performance obligations and allocating transaction prices due to contract changes and inter-departmental coordination. This case study enhances understanding of PSAK 72 implementation in the construction sector, particularly regarding the role of organizational factors in accounting decision-making. PT. Prambanan Dwipaka has demonstrated efforts to implement the standard, but still requires improvements in documentation and internal controls. Future case studies are recommended to involve more companies to provide a more comprehensive picture of PSAK 72 implementation in Indonesia.